Extensions of the Boundaries of Accounting Theory (Book). - Zeff, Stephen A.; Churchill, N. C.; Stedry, A. C. (The Accounting Review, 1964)
Reviews the book "Extensions of the Boundaries of Accounting Theory," by Thomas R. Prince.